Esploration Of The Influence Of Marketing Mix Strategy On Repurchase Intention Of Motorcycle Products: A Consumer Perspective - Made Agiyasa; Irsandi, Irsandi; Suci Asfarani; Trenggono Pujo Sakti (Cita konsultindo, 2025)
The purpose of this study is to explore how marketing mix strategies influence repurchase intentions of motorcycle products from the consumer's perspective. The research approach used in this study is a qualitative approach. This approach aims to understand the phenomenon in depth through the perspective of the participants. Qualitative research allows for in-depth exploration of consumer experiences, views, and perceptions related to marketing mix strategies and their influence on motorcycle product repurchase intentions. Based on the results of the study, it can be concluded that the 7P marketing mix strategy involving elements of product, price, promotion, distribution, people, process, and physical evidence has a significant influence on motorcycle repurchase intentions from a consumer perspective. Each element of the 7Ps plays a role in creating a positive consumer experience, which ultimately increases loyalty and repurchase decisions. Keywords: Marketing, Marketing Mix, Repurchase Intention